A Polygeneration Process Concept for Hybrid Solar and Biomass Power Plant : Simulation, Modeling, and Optimization. - Sahoo, Umakanta (John Wiley & Sons, Incorporated, 2018)
The global warming phenomenon as a significant sustainability issue is gaining worldwide support for development of renewable energy technologies. The term "polygeneration" is referred to as "an energy supply system, which delivers more than one form of energy to the final user." For example, electricity, cooling and desalination can be delivered from a polygeneration process. The polygeneration process in a hybrid solar thermal power plant can deliver electricity with less impact on the environment compared to a conventional fossil fuel-based power generating system. It is also THE next generation energy production technique with the potential to overcome the undesirable intermittence of renewable energy systems. In this study, the polygeneration process simultaneous production of power, vapor absorption refrigeration (VAR) cooling and multi-effect humidification and dehumidification (MEHD) desalination system from different heat sources in hybrid solar-biomass (HSB) system with higher energy efficiencies (energy and exergy), primary energy savings (PES) and payback period are investigated, focusing on several aspects associated with hybrid solar-biomass power generation installations, such as wide availability of biomass resources and solar direct normal irradiance (DNI), and other technologies. Thermodynamic evaluation (energy and exergy) of HSB power has also been investigated, along with the VAR cooling system, the modelling, simulation, optimization and cost analysis of the polygeneration hybrid solar biomass system, all accompanied by multiple case studies and examples for practical applications. This volume provides the researcher, student and engineer with the intellectual tool needed for understanding new ideas in this rapidly emerging field. The book is also intended to serve as a general source and reference book for the professional (consultant, designer, contractor etc.) who is working in the field of solar thermal, biomass, power plant, polygeneration, cooling and process heat. It is a must-have for anyone working in this field.